A sodium ion battery sodium-rich oxide positive electrode material and a preparation method thereof

CN122889737APending Publication Date: 2026-10-09CHENG DU TAN HE LI KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611379562.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,迄今为止,对高能量密度的富钠氧化物正极材料(简称富钠正材)的关注和研究较少,因为过多的钠含量会引起残碱较高,导致加工性能变差,同时富钠正材的固溶体结构在充放电过程中会产生多种相转变,引起结构塌陷,最终导致容量下降和循环恶化

Benefits of technology

[0025]当包覆剂的尺寸>50nm时,会产生包覆剂在溶剂里面分散不均匀,出现沉降或分层现象,最终导致包覆厚度和重量难以精确控制。雾化液滴尺寸>5μm,容易造成包覆物质不均匀,导致被包覆物质团聚在一起,降低了包覆层保护富钠正材基体的保护效果;雾化液滴尺寸<1μm,容易形飘散在空气中,很难被包覆物质吸附,从而不能有效包覆。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889737A_ABST
    Figure CN122889737A_ABST
Patent Text Reader

Abstract

The application relates to a sodium-rich oxide positive electrode material of a sodium ion battery and a preparation method thereof, and the sodium-rich oxide positive electrode material of the sodium ion battery comprises a base material and a coating layer, the base material is mainly composed of a sodium source, a M main element compound and a N doped element compound, M is at least one element in Ni, Mn, Fe, Co, Al and Zn, and N is at least one element in Ti, Cu, Zr, Cs, Mo, Sn, Zn, Ca, Li, Ru, K, In, Se, Sr, B, Te, Sb, La, Gd, Nb, W, F and P. The high-entropy doping technology is adopted in the positive electrode material, the phase transition of the sodium-rich oxide positive electrode material is inhibited, the discharge capacity, the cycle life are improved, and the problem of voltage attenuation is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium-ion batteries, and in particular, to a sodium-rich oxide cathode material for sodium-ion batteries and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have inherent advantages in low-temperature performance, rate performance, safety and cost. The battery system realizes energy storage based on the reversible migration of sodium ions between the cathode and anode. Its electrochemical principle is similar to that of lithium-ion batteries, but the abundance of sodium element in the earth's crust (2.74%) is significantly higher than that of lithium (0.0065%), giving it a prominent cost advantage. Technically, sodium-ion batteries exhibit excellent high and low temperature characteristics (-40°C to 80°C), intrinsic safety characteristics, and deep discharge storage capacity. Meanwhile, they outperform lithium-ion batteries in high-rate (above 50C) charge and discharge performance. This endows sodium-ion batteries with significant competitiveness in application scenarios such as large-scale energy storage power stations, new energy vehicles, start-up power sources and low-speed vehicles. It is particularly worth noting that with the optimization of material systems and the emergence of scale effects in the industrial chain, the watt-hour cost of sodium-ion batteries is expected to be further reduced. Gradually replacing traditional lead-acid batteries in fields such as two-wheel vehicles and start-up power has formed a clear industrialization trend, thereby building a diversified battery technology ecology complementary to lithium-ion batteries.

[0003] However, the energy density of existing sodium-ion batteries is lower than that of lithium-ion batteries. One of the main reasons is that the specific capacity of cathode materials for sodium-ion batteries is relatively low. Currently, common cathode materials for sodium-ion batteries on the market are mainly divided into two categories: polyanionic compounds and oxides. The former includes sodium iron phosphate composite (NFPP, with a theoretical specific capacity of 129 mAh / g), sodium iron sulfate (Na2Fe2(SO4)3, with a theoretical specific capacity of 121 mAh / g), and sodium vanadium phosphate (Na3V2(PO4)3, with a theoretical specific capacity of 117 mAh / g); the latter includes oxide Na x Fe y M z O2, where 0≤x, y, z≤1, with a theoretical specific capacity of about 240 mAh / g). The sodium-rich oxide cathode material Na 1+x M 1-x O2 (0<x<1, M is at least one selected from Ni, Mn, Fe, Co, Al and Zn), generally has a theoretical capacity of over 300 mAh / g. However, to date, there has been little attention and research on high-energy-density sodium-rich oxide cathode materials (referred to as sodium-rich cathode materials), because excessive sodium content will cause high residual alkali, leading to deteriorated processing performance. Meanwhile, the solid solution structure of sodium-rich cathode materials will undergo multiple phase transitions during charge and discharge, causing structural collapse, and ultimately leading to capacity decline and cycle performance deterioration.

[0004] In view of the above, the present invention is specifically proposed. Summary of the Invention

[0005] The first object of the present application is to provide a sodium-rich oxide cathode material for sodium-ion batteries. This solution adopts high-entropy doping technology to inhibit the phase transition of the sodium-rich oxide cathode material, increase the discharge capacity and cycle life, and alleviate the problem of voltage attenuation. The prepared sodium-rich cathode material has a high discharge capacity of 195 mAh / g, with an average plateau voltage of 3.2 V, and its theoretical energy density exceeds the current energy density of 200 Wh / kg lithium iron phosphate, which can realize large-scale promotion and application in fields requiring high energy density.

[0006] The second object of the present application is to provide a preparation method of the above-mentioned sodium-rich oxide cathode material for sodium-ion batteries. In this preparation method, there is no need to synthesize a precursor. Instead, salts are directly used as raw materials to obtain dry powder through wet grinding and spray drying, followed by one-step high-temperature sintering, wet coating and secondary sintering. The production efficiency is increased by more than 5 times, the processing cost of the cathode material is reduced by more than 60%, and the residual alkali is reduced to about 0.5%, which can be widely popularized and applied on existing lithium iron phosphate production lines.

[0007] In order to achieve the above object, the present invention provides a sodium-rich oxide cathode material for sodium-ion batteries, comprising: a base material and a coating layer, wherein the base material is mainly composed of a sodium source, a main M element compound, and an N doping element compound, M is at least one element selected from Ni, Mn, Fe, Co, Al, and Zn, and N is at least one element selected from Ti, Cu, Zr, Cs, Mo, Sn, Zn, Ca, Li, Ru, K, In, Se, Sr, B, Te, Sb, La, Gd, Nb, W, F, and P; The chemical formula of the coating layer is Π y O z , wherein 0 < y ≤ 3, 0 ≤ z ≤ 5, Π is a coating element, and Π is at least one element selected from Al, Mg, Ti, Zr, Sn, Ca, Na, Se, W, F, P, Ce, Zn, and B.

[0008] The main M element compound mainly provides discharge capacity and maintains structural stability, and the content of M can be increased or decreased according to the required capacity and cycle characteristics. The N doping element compound functions to reduce residual alkali and reduce phase transition during charge and discharge.

[0009] Preferably, as a further implementable solution, the chemical formula is Na 1+a M x N 1-x-a O2·Π y O z , wherein 0 < a ≤ 0.2 and 0 < x ≤ 1.2.

[0010] In the prior art, when a sodium-ion battery oxide cathode material is charged to above 4.0V, it will cause the migration of Fe ions and induce the formation of PO2 phase, thus leading to an increase in the impedance of sodium-ion batteries. When the sodium molar ratio x in the sodium-rich cathode material is >1.0, the excess sodium will enter the transition metal layer to form a solid solution structure. When sodium ions in the sodium metal layer undergo deintercalation, the sodium ions in the transition metal layer can prevent transition metal ions from migrating to the sodium metal layer, thereby maintaining structural stability and inhibiting the formation of PO2. When the sodium molar ratio x≥1.2, excessive sodium occupies transition metal atoms in the metal layer, resulting in a decrease in the proportion of electrochemically active metal atoms, which leads to a reduction in the discharge capacity of the sodium-rich cathode material. Moreover, excessive sodium content easily causes excessive residual alkali and degraded processing performance. Therefore, in Na 1+x M 1-x O2 sodium-rich cathode material, the reason why the sodium to metal ratio is controlled within the range of 0<x≤1.2 in the present invention is to obtain good electrochemical performance and processing characteristics. Therefore, the above range is finally obtained by the inventor after a great deal of creative work.

[0011] Preferably, as a further implementable solution, the M main element compound is at least one selected from the group consisting of nickel oxide, nickel hydroxide, manganese oxide, manganese hydroxide, iron oxide, iron hydroxide, aluminum oxide, aluminum hydroxide, zinc oxide and zinc hydroxide.

[0012] Preferably, as a further implementable solution, the N doping element compound contains at least five elements selected from the group consisting of titanium oxide, titanium hydroxide, copper oxide, copper hydroxide, zirconium oxide, zirconium hydroxide, cesium oxide, cesium hydroxide, metallic molybdenum, ammonium molybdate, tin oxide, tin hydroxide, zinc oxide, zinc hydroxide, calcium oxide, calcium hydroxide, lithium oxide, lithium carbonate, lithium hydroxide, ruthenium oxide, ruthenium hydroxide, potassium oxide, potassium carbonate, potassium hydroxide, indium oxide, indium hydroxide, selenium oxide, strontium oxide, strontium hydroxide, boric acid, boron oxide, tellurium oxide, antimony oxide, lanthanum oxide, gadolinium oxide, niobium oxide, tungsten oxide, ammonium tungstate, ammonium fluoride, sodium fluoride, phosphorus pentoxide and diammonium hydrogen phosphate.

[0013] In the solution of the present invention, doping with at least five element compounds is adopted to realize the synergistic effect of multiple elements, form a solid solution structure with stable structure, reduce the content of surface residual alkali (NaOH and Na2CO3) of the sodium-ion battery cathode material, and improve the thermal stability and electrochemical performance of the cathode material. For example, Li, Sn and Ti atoms can reduce Na in the sodium-ion battery cathode material + ions exchange with H in moisture + ion exchange, thereby reducing the surface residual alkali content of the sodium-ion battery cathode material. P 5+ ions have high electronegativity and can form stable compounds with sodium ions, thereby preventing Na + ions from reacting with H in water+ Ion exchange reduces residual alkali content. Cu and Sb atoms can form a superlattice structure, preventing H2O molecules from diffusing into the sodium electrode material, thus reducing residual alkali content and improving processing performance and high-temperature storage performance. Rb has a large ionic radius, which can increase the interlayer spacing of sodium metals and reduce the interlayer spacing of transition metals, increasing Na... + The diffusion coefficient is improved, thus reducing the residual alkali on the surface of the sodium electrode material. In summary, for example, a synergistic combination of six elements—Li, Sn, Ti, Cu, Sb, and Rb—can effectively reduce residual alkali.

[0014] Furthermore, for example, Ba, Mg, and Zr atoms can form high oxygen bonding bonds with oxygen atoms, thus suppressing oxygen release at a high voltage of 4.3V and reducing interfacial side reactions. This reduces gas production in sodium-ion battery cathode materials and improves their thermal safety characteristics. Sb, Cs, Ce, Nb, and Y atoms can suppress the migration of transition metal ions during cycling and prevent cell volume expansion or contraction, suppressing the voltage plateau drop after cycling and thus improving the energy density characteristics of sodium-ion battery cathode materials. Therefore, the effective combination of eight doping atoms—Ba, Mg, Zr, Sb, Cs, Ce, Nb, and Y—can suppress the O3-O'3-P3-P'3-P3 phase transition at high voltage, thereby improving the cycle life of sodium-rich cathode materials and reducing the voltage drop. These are all effective combinations.

[0015] Preferably, as a further feasible option, the coating layer is at least one selected from aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, titanium oxide, titanium hydroxide, zirconium oxide, zirconium hydroxide, tin oxide, tin hydroxide, calcium oxide, calcium hydroxide, calcium oxide, sodium hydroxide, sodium carbonate, selenium oxide, tungsten oxide, ammonium tungstate, cerium oxide, cerium hydroxide, boric acid, boron oxide, and silicon oxide.

[0016] The coating layer effectively prevents the electrolyte from corroding the substrate and damaging the structure, and it also reduces manganese leaching and the Taylor effect, thereby improving voltage drop. However, the coating layer should ideally be controlled within a certain range. Too thin a coating layer will result in poor protective performance, while too thick a coating layer will hinder sodium ion migration, leading to a decrease in capacity and cycle life, thus negatively impacting the electrochemical performance of sodium-ion batteries.

[0017] Preferably, as a further feasible option, the mass percentage of the coating layer is 0.05 to 1% of the total mass of the cathode material.

[0018] This invention also provides a method for preparing the above-mentioned sodium-rich oxide cathode material for sodium-ion batteries, comprising the following steps: Sodium source, M main element compound, N doped element compound, and deionized water are mixed and then ground into a slurry by passing an inert protective gas through the mixture. The slurry is then spray-dried to obtain a solid powder to form the substrate. The solid powder is sintered once, coated with a coating agent solution by wet atomization to form the coating layer, and then sintered a second time.

[0019] Traditional sodium-ion battery cathode material preparation technology involves a single high-temperature sintering process using a precursor such as NiFeMn(OH)2, Na2CO3, and additives, followed by pulverization, coating, secondary sintering, and pulverization to obtain the target material. The synthesis of the NiFeMn(OH)2 precursor typically involves reacting a NiFeMn sulfuric acid solution with a sodium hydroxide solution under specific pH, concentration, stirring speed, and temperature parameters, followed by centrifugation, washing, and drying. This process generally takes about 7 days. Therefore, not only is the production cycle long, but it also generates wastewater, waste liquid, and solid waste. Furthermore, the multiple processes result in high equipment investment, high processing costs, and complex process control.

[0020] The preparation method of this invention eliminates the above-mentioned problems by employing a one-step solid-state sintering technique without precursors. It improves the processing performance of sodium-rich cathode materials and suppresses phase transitions during cycling by adding a higher sodium ratio, additives to reduce residual alkali, and doping / coating elements to stabilize the phase structure. This improves the discharge capacity, cycle life, and reduces voltage decay of the sodium-rich cathode material. Specifically, it directly uses materials such as NiO, FeO, MnO, Na2CO3, and additives, followed by wet grinding and spray drying. Then, a first high-temperature sintering, wet coating, and a second low-temperature sintering are all performed in the same rotary kiln. This not only shortens the production cycle of sodium-ion battery cathode materials but also significantly reduces production costs.

[0021] Preferably, as a further feasible option, the slurry has a particle size D50 of 50-500 nm, the spray drying temperature is 200-300 °C, the spray drying time is 1-30 s, and the solid powder has a particle size of 1-30 μm.

[0022] In this invention, the grinding particle size is generally D50 = 50-500 nm. While a particle size smaller than 50 nm provides good low-temperature rate performance, it also increases the contact area between the sodium-rich cathode and the electrolyte, leading to gas generation, poor high-temperature storage performance, and decreased cycle performance. Conversely, a particle size larger than 500 nm results in uneven mixing of Na, M, and N elements, leading to unstable phase structures and impurities, resulting in excessively high residual alkali, increased impedance, and decreased discharge capacity. Therefore, a suitable particle size range should be selected based on the power, cycle life, and capacity of the sodium-rich cathode.

[0023] Preferably, the inert gas used in this invention is N2, Ar, or a mixture of both. This is to prevent oxidation reactions of some elements in M ​​and N, and to avoid low discharge capacity and structural collapse in sodium-rich positive materials, such as Fe. 2+ It is easily oxidized to Fe in the air. 3+ This leads to the deterioration and elemental segregation of the sodium-rich positive material, causing the electrochemical properties to fail.

[0024] Preferably, as a further feasible option, the temperature of the first sintering is 850~1000℃, the holding time is 8~15h, the size of the coating agent is ≤50nm, the size of the atomized droplets is 1-5μm, and the temperature of the second sintering is 300~750℃, the holding time is 3~10h.

[0025] When the size of the coating agent is greater than 50 nm, uneven dispersion of the coating agent in the solvent can occur, leading to sedimentation or stratification, ultimately making it difficult to precisely control the coating thickness and weight. Atomized droplet sizes greater than 5 μm easily cause uneven coating, resulting in the coated material agglomerating and reducing the protective effect of the coating layer on the sodium-rich substrate. Atomized droplet sizes less than 1 μm easily disperse in the air and are difficult to be adsorbed by the coating material, thus failing to provide effective coating.

[0026] In summary, the sodium-rich oxide cathode material for sodium-ion batteries prepared in this invention has a wide range of applications in the preparation of sodium-ion batteries.

[0027] Other features and advantages of this application will be described in detail in the following detailed description section.

[0028] Compared with the prior art, the technical effects of the present invention are as follows: 1. This invention adopts a one-step solid-state sintering technology without precursors, which can eliminate the need for equipment such as precursor synthesis, mixing, coating, and secondary kiln sintering, greatly improving production efficiency and reducing equipment investment. The cost of the sodium-rich cathode material prepared is only about 60% of that prepared by traditional technology, and the overall production efficiency is increased by more than 5 times. Moreover, the particle size and morphology of the sodium-rich cathode material can be controlled, and a nanoscale homogeneous structure and uniform nanolayer coating can be achieved. 2. Adding high-entropy doped elements to suppress residual alkali ensures that the sodium-rich positive material has a low residual alkali (around 0.5%) and improves the processing performance of the sodium-rich positive material. Therefore, it can be coated normally on existing lithium iron phosphate production lines without producing the "jelly" phenomenon. 3. The addition of high-entropy doped elements to suppress phase transition improves the discharge capacity, cycle life, and voltage decay suppression of the sodium-rich cathode at high voltages. The prepared sodium-rich cathode exhibits a high discharge capacity (195 mAh / g), a plateau voltage of 3.2 V, and a theoretical energy density of 195 mAh / g. 3.2 1 / 2 = 312Wh / kg, which exceeds the current energy density of lithium iron phosphate at 200Wh / kg. Attached Figure Description

[0029] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 SEM image of the sodium-rich positive material for sodium-ion batteries prepared in Example 1 of this invention; Figure 2 SEM image of the sodium-ion battery positive material prepared in Comparative Example 1; Figure 3 The above are capacity curves of the sodium-ion battery positive materials prepared in Example 1 and Comparative Example 1 of this invention. Figure 4 The cycling curves of the sodium-ion battery positive materials prepared in Example 1 and Comparative Example 1 of this invention are shown. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are only some embodiments of the present invention, not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0032] Example 1 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.20 Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 Li 0.01 B 0.005 The preparation method of O2·(Al+Zr+Ti)O2 includes the following steps: S1: According to the molar amounts of elements in the molecular formula, Na2CO3, NiO, FeO, MnO, ZnO and dopants CuO, ZrO2, CaO, Li2CO3 and B2O3 are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 60%. The slurry is ground to the target particle size D50=50nm using a vertical sand mill with N2 protective gas. Then the slurry is heat-treated in a spray drying equipment at a temperature of 300℃ for 30s, and finally a solid powder with a particle size of 3.5μm is obtained. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, and a high-temperature sintering, wet coating, and low-temperature sintering are completed sequentially. The first sintering temperature is 1000℃, and the holding time is 8h. The first sintered sample is wet coated by spraying with an atomized aqueous solution of coating agent (Al2O3, ZrO2, and TiO2) with a solid content of 30%. The droplet size after atomization is 5μm. The amount of coating agent is based on (Al+Zr+Ti) accounting for 1% of the total mass of the cathode material, where the molar ratio of Al, Zr, and Ti is 1:1:1. The particle size of the coating agent is less than 50nm. The coated sample is then subjected to a second low-temperature sintering at 750℃ for 3h. After the second sintering, the material is crushed and sieved to obtain a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 3.5μm.

[0033] Example 2 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.05 Ni 0.60 Co 0.15 Al 0.10 Ti 0.03 Cs 0.01 Mo 0.01 Sn 0.01 Zn 0.02 Ca 0.02 The preparation method of O2·(Al+Mg+Sn+Ca)O2 includes the following steps: S1: According to the molar amounts of elements in the molecular formula, NaHCO3, Ni(OH)2, CoO, Al2O3 and dopants Cs2O, TiO2, MoO3, SnO2, ZnO and CaO are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 40%. The slurry is ground to the target particle size D50=500nm using a vertical sand mill with Ar protective gas. Then the slurry is heat-treated in a spray drying equipment at a temperature of 200℃ for 1s, and finally a solid powder with a particle size of 30μm is obtained. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, and a high-temperature sintering, wet coating, and low-temperature sintering are completed sequentially. The first sintering temperature is 850℃, and the holding time is 15h. The first sintered sample is wet coated by spraying with an atomized aqueous solution of coating agent (Al2O3, MgO, SnO2, and Ca(OH)2) with a solid content of 10%. The droplet size after atomization is 1μm. The amount of coating agent is based on (Al+Mg+Sn+Ca) accounting for 0.05% of the total mass of the cathode material, where the molar ratio of Al, Mg, Sn, and Ca is 1:1:1:1. The particle size of the coating agent is less than 50nm. The coated sample is then subjected to a second low-temperature sintering at 300℃ for 10h. After the second sintering, the material is crushed and sieved to obtain a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 30μm.

[0034] Example 3 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.18 Fe 0.50 Mn 0.12 Al 0.10 Ru 0.01 K 0.02 In 0.01 Se 0.02 Sr 0.02 Te 0.02 O2·(Ca+Na+Se+W)O2, the preparation method includes the following steps: S1: According to the molar amounts of elements in the molecular formula, NaOH, Fe(OH)2, MnO, Al2O3 and dopants RuO2, K2CO3, In2O3, SeO2, SrO, and TeO2 are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 45%. The slurry is ground to the target particle size D50=100nm using a vertical sand mill with a mixed protective gas of 50% N2 and 50% Ar. Then, the slurry is heat-treated in a spray drying equipment at a temperature of 250℃ for 20s to finally obtain a solid powder with a particle size of 15μm. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, where a first high-temperature sintering, wet coating, and a second low-temperature sintering are sequentially completed. The first sintering temperature is 950℃, and the holding time is 12 hours. Coating agents (Ca(OH)2, NaOH, SeO2, and (NH4)6W7O) are used. 24A wet coating method was used to spray the calcined sample with an atomized ethanol solution containing 15% (·6H2O) and the droplet size after atomization was 3μm. The amount of coating agent was based on (Ca+Na+Se+W) accounting for 0.08% of the total mass of the cathode material, where the molar ratio of Ca, Na, Se and W was 1:1:1:1. The particle size of the coating agent was less than 50nm. The coated sample was then subjected to a second low-temperature sintering at 600℃ for 5h. After calcination, the material was crushed and sieved to obtain a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 15μm.

[0035] Example 4 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.20 Ni 0.10 Fe 0.55 Mn 0.0.05 Sb 0.03 La 0.02 Gd 0.01 Nb 0.01 W 0.03 O 1.80 F 0.20 The preparation method of (Al)O2 includes the following steps: S1: According to the molar amounts of elements in the molecular formula, NaNO3, Ni(OH)2, FeO, MnO and dopants Sb2O3, La2O3, Gd2O3, NbO2, WO3 and NaF are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 55%. The slurry is ground to the target particle size D50=220nm using a vertical sand mill with a mixed protective gas of 50%N2 and 50%Ar. Then the slurry is heat-treated in a spray drying equipment at a temperature of 250℃ for 20s, and finally a solid powder with a particle size of 15μm is obtained. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, and a high-temperature sintering, wet coating, and low-temperature sintering are completed sequentially. The first sintering temperature is 900℃, and the holding time is 10h. The first sintered sample is wet coated by spraying with an atomized ethanol solution of Al(OH)3 coating agent with a solid content of 15%. The atomized droplet size is 3μm, and the amount of coating agent is based on Al accounting for 0.08% of the total mass of the cathode material. The particle size of the coating agent is less than 50nm. The coated sample is then subjected to a second low-temperature sintering at 550℃ for 8h. After the second sintering, the material is crushed and sieved to obtain a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 8μm.

[0036] Example 5 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.20 Ni 0.40Fe 0.20 Mn 0.0.10 Zr 0.03 Sn 0.02 Ca 0.01 K 0.01 P 0.03 The preparation method of O2·(Al+Ti+Ce+W)O2 includes the following steps: S1: According to the molar amounts of elements in the molecular formula, Na2CO3, NaOH, Ni(OH)2, FeO, MnO and dopants ZrO2, SnO2, CaO, KOH and (NH4)2HPO4 are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 40%. The slurry is ground to the target particle size D50=80nm using a vertical sand mill with N2 mixed protective gas. Then the slurry is heat-treated in a spray drying equipment at a temperature of 180℃ for 15s to finally obtain a solid powder with a particle size of 5μm. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, where a first high-temperature sintering, wet coating, and a second low-temperature sintering are sequentially completed. The first sintering temperature is 980℃, and the holding time is 8 hours. The coating agents used are Al(OH)3, TiO2, CeO2, and (NH4)6W7O. 24 A wet coating method was used to spray the first-burned sample with an atomized ethanol solution containing 12% Al (6H2O) and a droplet size of 4μm. The amount of coating agent was 0.08% of the total mass of the cathode material (Al+Ti+Ce+W), with a molar ratio of Al, Ti, Ce and W of 1:1:1:1. The particle size of the coating agent was less than 50nm. The coated sample was then subjected to a second low-temperature sintering at 400℃ for 10h. After pulverization and sieving, a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 15μm was obtained.

[0037] Example 6 A high-capacity sodium-ion battery sodium-rich oxide cathode material, with the chemical formula Na 1.20 Ni 0.35 Fe 0.30 Mn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 Li 0.01 B 0.005 The preparation method of O2·(Al+Zr+Ti)O2 includes the following steps: S1: According to the molar amounts of elements in the molecular formula, Na2CO3, NiO, FeO, MnO and dopants CuO, ZrO2, CaO, Li2CO3 and B2O3 are placed in a mixing tank, deionized water is added, and the solid content of the slurry is adjusted to 60%. The slurry is ground to the target particle size D50=500nm using a vertical sand mill with N2 protective gas. Then the slurry is heat-treated in a spray drying equipment at a temperature of 280℃ for 30s, and finally a solid powder with a particle size of 5μm is obtained. S2: The above solid powder is conveyed into a rotary kiln purged with oxygen, and a high-temperature sintering, wet coating, and low-temperature sintering are completed sequentially. The first sintering temperature is 980℃, and the holding time is 10h. The first sintered sample is wet coated by spraying with an atomized aqueous solution of coating agent (Al2O3, ZrO2, and TiO2) with a solid content of 30%. The droplet size after atomization is 5μm. The amount of coating agent is based on (Al+Zr+Ti) accounting for 1% of the total mass of the cathode material, where the molar ratio of Al, Zr, and Ti is 1:1:1. The particle size of the coating agent is less than 50nm. The coated sample is then subjected to a second low-temperature sintering at 680℃ for 6h. After the second sintering, the material is crushed and sieved to obtain a high-capacity sodium-ion battery sodium-rich oxide cathode material with a particle size of 5μm.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is the molecular formula; all other processes are the same. The molecular formula of Comparative Example 1 is Na. 0.97 Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 Li 0.01 B 0.005 O2·(Al+Zr+Ti)O2 is not a sodium-rich oxide cathode material.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that high-entropy doping was not performed during the preparation process; only CuZrCa was doped, with the molecular formula Na. 1.20 Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 O2·(Al+Zr+Ti)O2, other processes are the same.

[0040] Experimental Example 1 The performance of the sodium-rich oxide cathode material products obtained in the above embodiments and comparative examples was tested using the following methods.

[0041] 1. Free sodium or residual alkali test: The free sodium or residual alkali test was performed using an automatic potentiometric titrator, model: METTLER TOLEDO G20. 5g of sample solvent was weighed into 40mL of aqueous solution, sonicated for 30min, filtered, and diluted to a 100mL volumetric flask. After shaking and standing, the supernatant was used for testing. The results are shown in Table 1.

[0042] 2. Structural characterization: The samples prepared in Example 1 and Comparative Example 1 were scanned by electron microscopy, and the SEM images are shown below. Figures 1-2 As shown. Figure 1 The text shows that the sodium-rich positive material particles in Example 1 are relatively dispersed and exhibit a single-crystal morphology, while... Figure 2 As can be seen from the comparison, the sodium-ion battery cathode material particles in Comparative Example 1 exhibit agglomeration and adhesion, failing to form a uniformly dispersed single-crystal morphology. This is because excess sodium salt is added during the synthesis of sodium-rich materials, and sodium salt itself acts as a flux, thereby lowering the melting point temperature of the single-crystal material growth. Therefore, at the same sintering temperature, sodium-rich cathode materials can form a better dispersed single-crystal morphology than non-sodium-rich cathode materials.

[0043] 3. Discharge capacity and cycle performance testing The positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) prepared in the examples and comparative examples were mixed at a mass ratio of 80:10:10. NMP was added to form a uniform slurry, which was then coated onto aluminum foil. After drying and rolling, the slurry was cut into positive electrode sheets with a diameter of 14 mm. A sodium-ion battery was assembled using a CR2032 button cell. The separator was made of glass fiber, the electrolyte was a 1 mol / L NaPF6 solution with EC / PC / DEC as the solvent, and the negative electrode was a sodium sheet. The sodium-ion battery test conditions were: temperature 25℃±1℃, charge / discharge cycle voltage range 2.0~4.3V, current 0.1C (170mAh / g), and cycle tests were conducted at 0.5C charge and 1C discharge. The results are shown in Table 1. Figures 3-4 As shown.

[0044] Table 1 Test Results

[0045] As shown in Table 1, the sodium-rich cathode materials prepared in Examples 1 to 6 have excellent discharge capacity and cycle performance, low residual alkali values, and voltage drops below 0.15mV. For example, the retention rate after 50 cycles is above 94%.

[0046] according to Figures 3-4 It can also be seen that Na in Example 1 1.20Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.0 1Li 0.01 B 0.005 The sodium-rich O2·(Al+Zr+Ti)O2 cathode material exhibited an initial discharge capacity of 197 mAh / g at 0.1C, a 50-cycle retention rate of 94.57%, and a voltage drop of 0.15 mV (as shown in Table 1). This indicates that the high-entropy doped sodium-rich structure can stabilize the phase structure, thus improving the voltage drop. In contrast, the non-sodium-rich Na cathode material in Comparative Example 1... 0.97 Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 Li 0.01 B 0.005 O2·(Al+Zr+Ti)O2 exhibits poor capacity, cycling performance, and voltage drop. Its initial capacity at 0.1C is only 167 mAh / g, with a 50-cycle retention of 92.22% and a voltage drop of 0.25 mV (as shown in Table 1). Comparative Example 2, using sodium-rich Na... 1.20 Ni 0.40 Fe 0.15 Mn 0.10 Zn 0.10 Cu 0.02 Zr 0.005 Ca 0.01 O2·(Al+Zr+Ti)O2, without high-entropy doping, has a high residual alkali content of 3.640%, indicating that the limited variety of dopants cannot produce a synergistic effect in reducing residual alkali. Due to the high surface alkali content, sodium ion insertion / extraction is inhibited, resulting in poor capacity and cycling performance. The discharge capacity is only 175 mAh / g, and the 50-cycle life is only 91.67%, with a large voltage drop of 0.21 mV, indicating that the limited variety of dopants cannot synergistically suppress phase transition. The above comparative data demonstrate that the one-step sintering technique without precursors and the high-entropy doping technique can suppress the phase transition of sodium-rich cathodes, improve discharge capacity and cycle life, and alleviate voltage decay issues. The prepared sodium-rich cathode has a low residual alkali value.

[0047] It should be noted that, where there is no conflict, the features in the embodiments of this application can be combined with each other.

[0048] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A sodium-rich oxide cathode material for sodium-ion batteries, characterized in that, include: The substrate and the coating layer, wherein the substrate is mainly composed of a sodium source, a main element compound (M), and a doped element compound (N), wherein M = at least one element selected from Ni, Mn, Fe, Co, Al, and Zn, and N = at least one element selected from Ti, Cu, Zr, Cs, Mo, Sn, Zn, Ca, Li, Ru, K, In, Se, Sr, B, Te, Sb, La, Gd, Nb, W, F, and P; The chemical formula of the coating layer is Π y O z , wherein 0 < y ≤ 3, 0 ≤ z ≤ 5, Π is a coating agent element, and Π is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Sn, Ca, Na, Se, W, F, P, Ce, Zn and B.

2. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 1, characterized in that, The chemical formula is Na 1+ a M x N 1-x-a O2·Π y O z , of which 0 <a≤0.2,0<x≤1.2。 3. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 1, characterized in that, The main element compound M is at least one of nickel oxide, nickel hydroxide, manganese oxide, manganese hydroxide, iron oxide, iron hydroxide, aluminum oxide, aluminum hydroxide, zinc oxide, and zinc hydroxide.

4. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 1, characterized in that, The N-doped element compound is at least five elements selected from titanium oxide, titanium hydroxide, copper oxide, copper hydroxide, zirconium oxide, zirconium hydroxide, cesium oxide, cesium hydroxide, metallic molybdenum, ammonium molybdate, tin oxide, tin hydroxide, zinc oxide, zinc hydroxide, calcium oxide, calcium hydroxide, lithium oxide, lithium carbonate, lithium hydroxide, ruthenium oxide, ruthenium hydroxide, potassium oxide, potassium carbonate, potassium hydroxide, indium oxide, indium hydroxide, selenium oxide, strontium oxide, strontium hydroxide, boric acid, boron oxide, tellurium oxide, antimony oxide, lanthanum oxide, gadolinium oxide, niobium oxide, tungsten oxide, ammonium tungstate, ammonium fluoride, sodium fluoride, phosphorus pentoxide, and diammonium hydrogen phosphate.

5. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 1, characterized in that, The coating layer is at least one of aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, titanium oxide, titanium hydroxide, zirconium oxide, zirconium hydroxide, tin oxide, tin hydroxide, calcium oxide, calcium hydroxide, calcium oxide, sodium hydroxide, sodium carbonate, selenium oxide, tungsten oxide, ammonium tungstate, cerium oxide, cerium hydroxide, boric acid, boron oxide, and silicon oxide.

6. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 1, characterized in that, The mass percentage of the coating layer is 0.05 to 1% of the total mass of the cathode material.

7. The method for preparing sodium-rich oxide cathode material for sodium-ion batteries according to any one of claims 1-6, characterized in that, Includes the following steps: Sodium source, M main element compound, N doped element compound, and deionized water are mixed and then ground into a slurry by passing an inert protective gas through the mixture. The slurry is then spray-dried to obtain a solid powder to form the substrate. The solid powder is sintered once, coated with a coating agent solution by wet atomization to form the coating layer, and then sintered a second time.

8. The preparation method according to claim 7, characterized in that, The slurry has a particle size D50 of 50-500 nm, the spray drying temperature is 200-300℃, the spray drying time is 1-30 s, and the solid powder has a particle size of 1-30 μm.

9. The sodium-rich oxide cathode material for sodium-ion batteries according to claim 7, characterized in that, The temperature of the first sintering is 850~1000℃, the holding time is 8~15h, the size of the coating agent is ≤50nm, the size of the atomized droplets is 1-5μm, and the temperature of the second sintering is 300~750℃, the holding time is 3~10h.

10. The application of the sodium-rich oxide cathode material for sodium-ion batteries according to any one of claims 1-6 and the sodium-rich oxide cathode material for sodium-ion batteries prepared by the preparation method according to any one of claims 7-9 in the preparation of sodium-ion batteries.